2019
DOI: 10.1167/iovs.18-25296
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Ganglion Cell-Inner Plexiform Layer Thinning in Normal, Open-Angle Glaucoma and Pseudoexfoliation Glaucoma Eyes: A Trend-Based Analysis

Abstract: The purpose of this study was to determine the rate of ganglion cell-inner plexiform layer (GCIPL) thinning by Cirrus high-definition optical coherence tomography (HD-OCT) in normal eyes and open-angle glaucoma (OAG) and pseudoexfoliation glaucoma (PXG) eyes. METHODS. This was a longitudinal observational study. We evaluated 282 subjects who visited a glaucoma clinic of a tertiary hospital in Korea: 60 healthy eyes, 193 medically treated OAG eyes, and 29 medically treated PXG eyes with a minimum 3-year follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…These values were then compared with those for abnormal conditions, particularly glaucoma, and the rate of reduction in glaucoma patients was found to be significantly higher than that in normal subjects. There was also a difference in the rate according to glaucoma status, which was reported to be in the range of approximately −0.5 ~ −1.0 μm/year [38][39][40][41] , and Lee et al 42 reported a rate of −1.46 μm/year in pseudoexfoliation glaucoma. The rate of GC-IPL loss in the control group in the present study (−0.277 µm/year) was consistent with the above studies, and the reduction rates in the no-DR and NPDR groups (−0.627 µm/year and −0.987 µm/year, respectively) were similar to those of glaucoma patients.…”
Section: Discussionmentioning
confidence: 97%
“…These values were then compared with those for abnormal conditions, particularly glaucoma, and the rate of reduction in glaucoma patients was found to be significantly higher than that in normal subjects. There was also a difference in the rate according to glaucoma status, which was reported to be in the range of approximately −0.5 ~ −1.0 μm/year [38][39][40][41] , and Lee et al 42 reported a rate of −1.46 μm/year in pseudoexfoliation glaucoma. The rate of GC-IPL loss in the control group in the present study (−0.277 µm/year) was consistent with the above studies, and the reduction rates in the no-DR and NPDR groups (−0.627 µm/year and −0.987 µm/year, respectively) were similar to those of glaucoma patients.…”
Section: Discussionmentioning
confidence: 97%
“…Shin et al 27 found that the rate of change in mean pRNFL thickness was − 1.26 μm/ year in patients with progressing glaucoma. Another study reported that the average RNFL thinning rate was − 1.31 μm/year in patients with pseudoexfoliative glaucoma 28 . Lee et al 25 reported that the reduction rate in the mean pRNFL thickness of the hypertension group was − 0.99 μm/year.…”
Section: Discussionmentioning
confidence: 98%
“…Rates of GCIPL thinning (Cirrus HD-OCT) have been reported between −0.28 to −0.92 μm/year when all levels of glaucoma damage are considered. 128,228,230,353 Lee et al investigated rates of GCIPL thinning after an average follow-up of 3 years; the mean rates of change were −0.31 μm/year in normal eyes, −0.49 μm/year in POAG eyes and −1.46 μm/year in eyes with pseudoexfoliation glaucoma. 228 Suda et al reported an average rate of change of −0.47 μm/year for GCC as measured with RTVue OCT in a longitudinal cohort of glaucoma patients with disease severity ranging from mild to severe (see below).…”
Section: Iv) Performance Of Macular Oct Imaging For Detecting Glaucoma Progressionmentioning
confidence: 99%
“…128,228,230,353 Lee et al investigated rates of GCIPL thinning after an average follow-up of 3 years; the mean rates of change were −0.31 μm/year in normal eyes, −0.49 μm/year in POAG eyes and −1.46 μm/year in eyes with pseudoexfoliation glaucoma. 228 Suda et al reported an average rate of change of −0.47 μm/year for GCC as measured with RTVue OCT in a longitudinal cohort of glaucoma patients with disease severity ranging from mild to severe (see below). 364 Mohammadzadeh and coworkers 269 investigated longitudinal rates of change for FMT, GCC, GCIPL and GCL in a cohort of glaucoma eyes with central or advanced damage at baseline.…”
Section: Iv) Performance Of Macular Oct Imaging For Detecting Glaucoma Progressionmentioning
confidence: 99%